Indirect model predictive current control techniques for a direct matrix converter - Rivera, Marco; Nasir, Usman; Tarisciotti, Luca; Wheeler, Patrick (2017)
The direct matrix converter has twenty-seven available switching states which implies that the implementation of predictive control techniques in this converter requires high computational cost while an adequate selection of weighting factors in order to control both input and output sides of the converter. In this paper, two indirect model predictive current control strategies are proposed in order to simplify the computational cost while avoiding the use of weighting factors. Both methods are based on the fictitious dc-link concept, which has been used in the past for the classical modulation and control techniques of the direct matrix converter. Simulated results confirm the feasibility of the proposed techniques demonstrating that they are an alternative to classical predictive control strategies for the direct matrix converter.